2021
DOI: 10.1051/0004-6361/202040239
|View full text |Cite
|
Sign up to set email alerts
|

The MUSE-Faint survey. II. The dark matter-density profile of the ultra-faint dwarf galaxy Eridanus 2

Abstract: Aims. We use stellar line-of-sight velocities to constrain the dark-matter density profile of Eridanus 2, an ultra-faint dwarf galaxy with an absolute V-band magnitude MV = −7.1 that corresponds to a stellar mass M* ≈ 9 × 104 M⊙. We furthermore derive constraints on fundamental properties of self-interacting and fuzzy dark matter scenarios. Methods. We present new observations of Eridanus 2 from MUSE-Faint, a survey of ultra-faint dwarf galaxies with the Multi Unit Spectroscopic Explorer on the Very Large Tele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 119 publications
1
15
0
Order By: Relevance
“…The dark photon exchange, on the other hand, causes the velocity independent self-interaction cross section σ 0 /m DM ∼ 4πα 2 D m DM /m 4 γ , which is of O(0.01-0.1) cm 2 /g. This cross section is consistent with the constraints, σ 0 /m DM 0.1-1cm 2 /g, obtained from the galaxy clusters [61][62][63][64][65][66][67][68][69], and, σ 0 /m DM 0.01-0.1cm 2 /g, obtained from the ultra-faint dwarf galaxies [70,71]. 15 14 Here, we assume that there is no asymmetry between the dark pion and the dark anti-pion, which is justified in the appendix B.…”
Section: Jhep07(2021)220supporting
confidence: 84%
“…The dark photon exchange, on the other hand, causes the velocity independent self-interaction cross section σ 0 /m DM ∼ 4πα 2 D m DM /m 4 γ , which is of O(0.01-0.1) cm 2 /g. This cross section is consistent with the constraints, σ 0 /m DM 0.1-1cm 2 /g, obtained from the galaxy clusters [61][62][63][64][65][66][67][68][69], and, σ 0 /m DM 0.01-0.1cm 2 /g, obtained from the ultra-faint dwarf galaxies [70,71]. 15 14 Here, we assume that there is no asymmetry between the dark pion and the dark anti-pion, which is justified in the appendix B.…”
Section: Jhep07(2021)220supporting
confidence: 84%
“…There is a long history of performing this type of analysis in local dwarfs (e.g. Kravtsov et al 1998;de Blok et al 2001;Goerdt et al 2006;Oh et al 2011Oh et al , 2015Read et al 2016bRead et al , 2018Read et al , 2019Karukes & Salucci 2017;Zoutendijk et al 2021), in spiral galaxies (e.g. Gentile et al 2004;Spano et al 2008;Donato et al 2009;Martinsson et al 2013a;Allaert et al 2017;Katz et al 2017;Korsaga et al 2018;Di Paolo et al 2019) or in massive early type galaxies often aided by gravitational lensing (e.g.…”
Section: Dm Halos Properties With Core or Cuspy Profilesmentioning
confidence: 99%
“…With MUSE-Faint (Zoutendijk et al 2020; hereafter Paper I), a survey of UFDs with MUSE (Bacon et al 2010), we are observing the spectroscopically unexplored centres of faint and ultra-faint satellites of the Milky Way. Previously, we have derived constraints on the dark-matter density profile of Eridanus 2 (Eri 2) and on the properties of self-interacting and fuzzy dark matter (Zoutendijk et al 2021; hereafter Paper II). While we could not resolve a core, we found that a core in Eri 2 must be smaller than ≈100 pc (95% confidence level), which is smaller than the cores found in larger dwarf galaxies.…”
Section: Introductionmentioning
confidence: 99%